Lifetime analysis of individual-atom contacts and crossover to geometric-shell structures in unstrained silver nanowires - Obermair, Christian; Kuhn, Holger; Schimmel, Thomas (Beilstein Journal of Nanotechnology, 2011)
We study the crossover of quantum point contacts from (i) individual-atom contacts to (ii) electronic-shell effects and finally to (iii) geometric-shell effects in electrochemically deposited silver contacts. The method allows the fabrication of mechanically unstrained structures, which is a requirement for determining the individual atomic configuration by means of a detailed lifetime analysis of their conductance. Within the geometric-shell model, the sequence of conductance maxima is explained quantitatively based on the crystal structure data of silver, and the growth mechanism of the nanowires is discussed.
Keywords: nanowires; quantum point contacts; shell effect; silver

(untitled) - Xie, F.-Q.; Nittler, L.; Obermair, C.; Schimmel, T. (Phys. Rev. Lett., 2004)

(untitled) - Xie, F.-Q.; Obermair, C.; Schimmel, T. (Solid State Commun., 2004)

Nanoscale Devices – Fundamentals and Applications - Xie, F.-Q.; Obermair, C.; Schimmel, T. (Springer, 2006)

(untitled) - Xie, F.-Q.; Maul, R.; Augenstein, A.; Obermair, C.; Starikov, E. B.; Schön, G.; Schimmel, T.; Wenzel, W. (Nano Lett., 2008)

(untitled) - Obermair, C. (Cuvillier Verlag, 2005)

(untitled) - Xie, F.-Q.; Maul, R.; Obermair, C.; Wenzel, W.; Schön, G.; Schimmel, T. (Adv. Mater., 2010)

(untitled) - Terabe, K.; Hasegawa, T.; Nakayama, T.; Aono, M. (Nature, 2005)

(untitled) - Beebe, J. M.; Kushmerick, J. G. (Appl. Phys. Lett., 2007)

(untitled) - Morales-Masis, M.; van der Molen, S. J.; Fu, T. W.; Hesselberth, M. B.; van Ruitenbeek, J. M. (Nanotechnology, 2009)

(untitled) - Hepel, M. (Russ. J. Electrochem., 2008)

(untitled) - Schirm, C.; Pernau, H.-F.; Scheer, E. (Rev. Sci. Instrum., 2009)

(untitled) - Agraït, N.; Levy Yeyati, A.; van Ruitenbeek, J. M. (Phys. Rep., 2003)

(untitled) - Xie, F.-Q.; Maul, R.; Brendelberger, S.; Obermair, C.; Starikov, E. B.; Wenzel, W.; Schön, G.; Schimmel, T. (Appl. Phys. Lett., 2008)

(untitled) - Cuevas, J. C.; Levy Yeyati, A.; Martín-Rodero, A. (Phys. Rev. Lett., 1998)

(untitled) - Pauly, F.; Dreher, M.; Viljas, J. K.; Häfner, M.; Cuevas, J. C.; Nielaba, P. (Phys. Rev. B, 2006)

(untitled) - Scheer, E.; Agraït, N.; Cuevas, J. C.; Yeyati, A. L.; Ludoph, B.; Martín-Rodero, A.; Bollinger, G. R.; van Ruitenbeek, J. M.; Urbina, C. (Nature, 1998)

(untitled) - Yanson, A. I.; Yanson, I. K.; van Ruitenbeek, J. M. (Nature, 1999)

(untitled) - Krans, J. M.; Muller, C. J.; Yanson, I. K.; Govaert, T. C. M.; Hesper, R.; van Ruitenbeek, J. M. (Phys. Rev. B, 1993)

(untitled) - Park, J.; Pasupathy, A. N.; Goldsmith, J. I.; Chang, C.; Yaish, Y.; Petta, J. R.; Rinkoski, M.; Sethna, J. P.; Abruña, H. D.; McEuen, P. L.; Ralph, D. C. (Nature, 2002)

(untitled) - de Heer, W. A. (Rev. Mod. Phys., 1993)

(untitled) - Lyalin, A.; Solov’yov, I. A.; Solov’yov, A. V.; Greiner, W. (Phys. Rev. A, 2007)

(untitled) - Yanson, A. I.; Yanson, I. K.; van Ruitenbeek, J. M. (Phys. Rev. Lett., 2001)

(untitled) - Mares, A. I.; van Ruitenbeek, J. M. (Phys. Rev. B, 2005)

(untitled) - Li, C. Z.; Tao, N. J. (Appl. Phys. Lett., 1998)

(untitled) - Li, C. Z.; Bogozi, A.; Huang, W.; Tao, N. J. (Nanotechnology, 1999)

Molecular Nanowires and Other Quantum Objects - Obermair, C.; Kniese, R.; Xie, F.-Q.; Schimmel, T. (Kluwer Academic Publishers, 2004)

(untitled) - Mészáros, G.; Kronholz, S.; Karthäuser, S.; Mayer, D.; Wandlowski, T. (Appl. Phys. A, 2007)

(untitled) - Reyes Calvo, M.; Mares, A. I.; Climent, V.; van Ruitenbeek, J. M.; Untiedt, C. (Phys. Status Solidi A, 2007)

(untitled) - Torres, J. A.; Pascual, J. I.; Sáenz, J. J. (Phys. Rev. B, 1994)

(untitled) - Stafford, C. A. (Phys. Status Solidi B, 2002)

(untitled) - Brandbyge, M.; Jacobsen, K. W.; Nørskov, J. K. (Phys. Rev. B, 1997)

(untitled) - Rodrigues, V.; Bettini, J.; Rocha, A. R.; Rego, L. G. C.; Ugarte, D. (Phys. Rev. B, 2002)

(untitled) - Yannouleas, C.; Bogachek, E. N.; Landman, U. (Phys. Rev. B, 1998)